Answers

2015-06-13T13:19:10+05:30
2x+3r=6
⇒2x=6-3r
⇒x= \frac{6-3r}{2} .....(1)
x+4r=4
substituting the value of x as  \frac{6-3r}{2} from....(1) we get:
 \frac{6-3r}{2} +4r=4
⇒6-3r+4r * 2 =4*2
⇒6-3r+8r=8
⇒5r=8-6
⇒r= \frac{2}{5}
Substituting the value of r as  \frac{2}{5} we get:
x+4r=4
⇒x=4-4r
⇒x=4- \frac{2*4}{5}
⇒x=4- \frac{8}{5}
⇒x= \frac{12}{5}
Ans:x= \frac{12}{5}
r= \frac{2}{5}  
--------------------------------------------------------------------------------------
Please mark as the best.
1 5 1